Analisis Kelayakan Pengembangan Industri Ulat Sutera : Studi Kasus di Kelompok Tani Sutera Alam Margowangsan, Sawangan, Kabupaten Magelang (Feasibility Study of Silkwarm Industry) - Rushandi Alvianus; Kuncoro Harto Widodo; Didik Purwadi (agriTECH, 1999)
This research investigated the feasibility study on the development of silkworm (ulat sutera) industry. First investigation was conducted on must aspect for demand and supply condition, product price, market share, and marketing strategy. Second, technical aspect includes product capacity, break even point, process technology, location, and lay out. Third, financial aspect was focused on the pay back period, profitability index, internal rate of return, and net present value. Finally, organization and management aspect was analyzed for company's effectivity and efficiency.